Numerical investigation of the effect of changing the geometry of a U-shaped fuel cell channel with asymmetric gas flow and its effect on hydrogen consumption - Yuan, Yanjie; Abdullah, M. M.; Sajadi, S. Mohammad; Heidarshenas, Behzad; Malekshah, Emad Hasani; Aybat, Hikmet S. (Pergamon-Elsevier Science Ltd, 2024)
In this study, the simulation of a fuel cell is done to investigate how to reduce hydrogen loss in a fuel cell. Hydrogen and oxygen enter two channels in opposite directions. This study focuses on reducing hydrogen loss using H-shaped channels by changing the width of its vertical and horizontal parts at different voltages in the range of 0.05-0.8 V. Also, the values of cell power, electrolyte potential, mole fraction (MOF) of water and oxygen, and MOF of hydrogen are estimated. The finite element method (FEM) and COMSOL software are used for the simulations. The results demonstrate that the reduction of electrolyte potential by increasing the voltage from 0.1 to 0.8 V for the channel widths of 2-5 cm is 76.6 %, 83.3 %, 75.6 %, and 69.7 %, respectively. By enhancing the width of the channel from 2 to 5 cm at the voltages of 0.1 and 0.8 V, the MOF of hydrogen is decreased by 1.9 % and 4.8 %, respectively. When the width of channels changes from 2 to 5 cm, the amount of cell power is reduced by 54.3 %, 53.5 %, 52.4 %, and 52.6 %, respectively, by changing the voltage from 0.3 to 0.8 V. By increasing the voltage from 0.1 to 0.8 V, the MOF of hydrogen is decreased by 23.8 %, 24.4 %, 21.8 %, and 30.2 %, respectively, for the channel width of 2-5 cm.
Keywords: Mole fraction of hydrogen; Fuel cell; Potential electrolyte; Power cell